Professional Training of Bachelors in Mechanical Engineering, Based on Networking Resources; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Loshchilova M. A. Marina Andreevna (2015, 2015)
Title screen